Teachers’ Attitude Towards the Use of Differentiated Instruction (DI) and its Impact On Teaching - Kumar Kharka, Deo; Kinley (Bhutan Journal of Research and Development, 2024)
A single-paced method of instruction does not benefit diverse learners, which is why "one size fits all" teaching has been severely criticized. Thus, it is essential to differentiate instruction to meet the diverse needs of learners. Using mixed methods, this study examines teachers’ use of DI and their attitudes towards using DI in the classroom. Additionally, the study examined the impact of teachers’ attitudes on the practice of DI and the challenges associated with it. Surveys, classroom observations, self-administered open-ended questionnaires, and student feedback were used to collect data. Teacher attitudes toward DI seem positive, and they understand it well. In the classroom, content, process, and product are typically differentiated, with product being the least differentiated. Teachers’ attitudes and DI implementation also exhibit a statistically significant positive correlation (rs (22) =.75, p ≤ .001). In addition, teachers’ attitudes influence DI implementation. Moreover, DI implementation is hampered by crowding, high student-teacher ratios, time constraints, and a rule forbidding student from using their mobile phones. This study raises awareness about DI in the school system in order to meet the needs of diverse learners, who may not benefit from a single-paced teaching approach.